Soft Skills Training to Become Professionals for Students at Samakisast Wittaya School in Sadao, Thailand - Dedy Mainata; Darmawati; Dharma Yanti; Arista Wibowo; Shamil Hekmatyar Siregar (LP2M of Institute for Research and Community Services - UIN Walisongo, 2025)
This community service program was conducted at Samakisast Wittaya School, Sadao, Thailand, to address the lack of students’ interpersonal readiness for higher education and employment. The activity aimed to strengthen soft skills such as professional demeanor, communication, teamwork, and courteous speech. Using participatory action research integrated with community-based research, service-learning, and asset-based community development, the one-day program engaged sixty students through tutorials and rotating practice stations focusing on appearance, posture, handshake protocol, and polite expressions. The results showed high participation, improved understanding of the importance of soft skills, and observable behavioral enhancement during coached demonstrations. Tangible outputs included behavioral rubrics and photo documentation for continued use. The program concludes that a participatory, low-cost, and asset-based model effectively embeds soft-skills training into school routines and can serve as a foundation for sustained teacher-led reinforcement and future quantitative evaluation.